On Some Expansion Formulas for Products of Jacobi’s Theta Functions - Hong-Cun Zhai; Jian Cao; Sama Arjika (Mathematics, 2023)
In this paper, we establish several expansion formulas for products of the Jacobi theta functions. As applications, we derive some expressions of the powers of <semantics>(q;q)∞</semantics> by using these expansion formulas.